Organizational aspects of rehabilitative care for patients with traumatic disease of the spinal cord - Z. R. Khaibullina (Бюллетень сибирской медицины, 2010)
Proposed organizational aspects of rehabilitative care for patients with traumatic disease of the spinal cord. Aim was to study the organization providing rehabilitation of spinal patients. Identified the following stages of rehabilitation services: a full-fledged conservative therapy, rehabilitation, improvement or compensation for lost functions, the restoration of household activity, the restoration of social activity. Properly set the organization of rehabilitation services, allows patients to our clinic undergo a complete rehabilitation, which greatly improved the results of treatment of this severe pathology.